The application of irreversible genomic states to define and trace ancient cell type homologies - Oleg Simakov; Günter P. Wagner (EvoDevo)
Abstract Homology, or relationship among characters by common descent, has been notoriously difficult to assess for many morphological features, and cell types in particular. The ontogenetic origin of morphological traits means that the only physically inherited information is encoded in the genomes. However, the complexity of the underlying gene regulatory network and often miniscule changes that can impact gene expression, make it practically impossible to postulate a clear demarcation line for what molecular signature should "define" a homologous cell type between two deeply branching animals. In this Hypothesis article, we propose the use of the recently characterized irreversible genomic states, that occur after chromosomal and sub-chromosomal mixing of genes and regulatory elements, to dissect regulatory signatures of each cell type into irreversible and reversible configurations. While many of such states will be non-functional, some may permanently impact gene expression in a given cell type. Our proposal is that such evolutionarily irreversible, and thus synapomorphic, functional genomic states can constitute a criterion for the timing of the origin of deep evolutionary cell type homologies. Our proposal thus aims to close the gap between the clearly defined homology of the individual genomic characters and their genomic states to the homology at the phenotypic level through the identification of the underlying evolutionarily irreversible and regulatory linked states.